2010
DOI: 10.1007/s00330-010-1997-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose from volumetric helical perfusion CT of the thorax, abdomen or pelvis

Abstract: The radiation dose imposed by perfusion CT was on average 1.5 times that of a CT thorax, abdomen and pelvis. The dose is not insubstantial, and must be balanced by the potential clinical utility of additional physiologic data. Further efforts towards dose reduction should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The radiation dose of our protocol is within the range of usual body CTP protocols in oncology. 44,45 Within the direct x-ray beam in prostatic CTP, the organ that is most vulnerable to radiation is the prostate itself, and no other sensitive organs are contained within the x-ray volume besides the bone marrow. The prostate is usually sought to undergo definitive therapy, either by surgery or by radiation therapy, and unlike in other oncological CTP applications, such as colorectal cancer or lung cancer, no functioning prostate parenchyma is left after therapy.…”
Section: Clinical Implementation and Radiation Burdenmentioning
confidence: 99%
“…The radiation dose of our protocol is within the range of usual body CTP protocols in oncology. 44,45 Within the direct x-ray beam in prostatic CTP, the organ that is most vulnerable to radiation is the prostate itself, and no other sensitive organs are contained within the x-ray volume besides the bone marrow. The prostate is usually sought to undergo definitive therapy, either by surgery or by radiation therapy, and unlike in other oncological CTP applications, such as colorectal cancer or lung cancer, no functioning prostate parenchyma is left after therapy.…”
Section: Clinical Implementation and Radiation Burdenmentioning
confidence: 99%
“…Kinetics, which can be recorded quantitatively, can provide useful data to monitor changes in tumor angiogenesis following therapy [42][43][44][45][46][47]. However, the technique is still limited by a higher ionizing radion dose than a standard CT study [48]. This has prevented more widespread uptake and perhaps the expectation that dosage will reduce with technological refinement partly explains the lack of multicenter studies, to date, to evaluate its use [49].…”
Section: Review Afaq and Akinmentioning
confidence: 98%
“…In our study, the mean effective radiation dose to each individual was 25.6 mSv, which is within the range of current oncological perfusion studies. [16] Main methodological limitations of CTP of the prostate are related to poor anatomical intraprostatic detail, its inability both to detect small tumors, and also to assess extracapsular extension of the disease. A recent en-bloc approach has shown that patients with high-grade and intermediate-grade PCa can be more precisely differentiated with CTP rather than with biopsy.…”
Section: Discussionmentioning
confidence: 99%